Non-Surgical treatment Versus Surgery for Iatrogenic Femoral Artery Pseudoaneurysms: Systematic Review and Meta-Analysis - Wu, Haoliang; Zhang, Liwei; Zhang, Cong; Xie, Boao; Lou, Chunyang; Liu, Yuanfeng; Bai, Hualong (Frontiers in Surgery, 2022)
Objectives: This study compared results of non-surgical treatment (compression and ultrasound guided thrombin injection (UGTI)) and surgery to treat iatrogenic femoral artery pseudoaneurysms. Methods: PubMed and Embase databases were searched up to October 2021. Primary outcome measure was success rate, and other outcomes examined were complication rate, reintervention rate. Two authors independently reviewed and extracted data. Data were presented as the odds ratios (ORs) with 95% confidence intervals (CIs). The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to appraise the quality of the body of evidence. Results: Eight studies were included. A total of 623 patients with pseudoaneurysm undergoing treatment were included, of which 163 subjects underwent surgery, 397 subjects underwent compression, and 63 subjects underwent UGTI. The success rate was significantly lower in the non-surgery group (OR 0.24, 95% CI 0.08 – 0.69, I2=0%). The complication rate was significantly lower in the non-surgery group (OR 0.10, 95% CI 0.03 –0.29, I2=0%). Patients in the non-surgery group tended to have a lower, but statistically insignificant, reintervention rate (OR 0.11, 95% CI 0.01 – 1.06, I2=35%). Further, the GRADE assessment showed that these results (success rate, complication rate, and reintervention rate) were of very low quality. Conclusions: Available evidence shows that it is reasonable to regard non-surgical treatment as the primary treatment for iatrogenic femoral artery pseudoaneurysms, and surgery as a remedy after failure of non-surgical treatment in some cases.